2003
DOI: 10.1017/s0950268802008075
|View full text |Cite
|
Sign up to set email alerts
|

Bartonella infection in sylvatic small mammals of central Sweden

Abstract: Sylvatic small mammals were captured in rural habitats near Uppsala, Sweden, to measure the prevalence of bartonella infections, characterize bacterial isolates and identify their host range, and increase our understanding of host-pathogen ecology. During 7 nights of trapping at 3 localities, 236 small mammals were captured (trap success 30%). Bartonella were isolated from bloods of Apodemus flavicollis (19 of 110 tested), Apodemus sylvaticus (6/25), Clethrionomys glareolus (9/60), Microtus agrestis (1/3), Mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
78
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 20 publications
9
78
0
1
Order By: Relevance
“…Many studies have reported similar, or even higher, prevalence of Bartonella in wild rodents in a variety of geographical locations (Kosoy et al, 1997;Fichet-Calvet, 2000;Ying et al, 2002;Holmberg et al, 2003).…”
Section: Discussionmentioning
confidence: 90%
“…Many studies have reported similar, or even higher, prevalence of Bartonella in wild rodents in a variety of geographical locations (Kosoy et al, 1997;Fichet-Calvet, 2000;Ying et al, 2002;Holmberg et al, 2003).…”
Section: Discussionmentioning
confidence: 90%
“…In Thailand, a number of the Bartonella isolates from Thai rodents are closely related to B. grahamii and B. elizabethae, two species that have been associated with human illness [36]. Bartonella grahamii has been mainly isolated from bank voles (Clethrionomys glareolus) in the United Kingdom [20] and Poland [10] and from yellow-necked mice (Apodemus flavicollis) in Sweden [110], but has also been isolated from rats in the USA and a domestic mouse captured in California [77]. The rodent flea Ctenophthalmus nobilis was recently shown to be a competent vector of at least two Bartonella species, B. grahamii, which has previously been associated with human ocular infection (neuroretinitis and retinal artery occlusion) [123,208], and B. taylorii [23].…”
Section: Rodent-borne Zoonotic Bartonellaementioning
confidence: 99%
“…These gltA amplicon sequences differed from those described for all the known Bartonella variants. F15YN had the highest BLAST sequence similarity (97%) to Bartonella strains detected from rodents from Greece (Tea et al, 2004) and Sweden (Holmberg et al, 2003) and 95% similarity to B.…”
Section: Pcr Detection Of Bartonella Dna In Rodent Fleasmentioning
confidence: 99%